Identificación macroscópica de patologías provocadas por la fasciola hepática en bovinos faenados en el camal municipal de Babahoyo - Meza Peralta, Erika Lissbeth (2023)
The present research work was carried out in the Babahoyo municipal slaughterhouse, province of Los Ríos, with the objective of macroscopic identification of the pathologies caused by hepatic fluke in cattle slaughtered in the municipal slaughterhouse. Furthermore, the variables we study are; the sex, breed, age and origin of the animal. The sample size was 500 cattle, the methodology used was the Chi Square design. To determine the changes that occur in the liver, the origin, race, sex, age must be considered, and the various changes found in the liver must be identified in order to evaluate the loss due to confiscation. The Fasciola remains alive in the liver. During the post-mortem analysis, it achieves a very dark coloration of the skin surface where the tissue becomes soft and friable and indicates that the walls of the organ are hyperplastic. We can observe the economic losses of the liver caused by hepatic fasciola lesions, where 10 livers from 500 samples collected were seized, weighing 105lbs in total and an economic loss of $316.25 dollars, considering that a pound of liver is valued at $2,75